PERAN UNIT KAMSEL MELALUI DIKMAS LANTAS SEBAGAI UPAYA MENEKAN ANGKA PELANGGARAN LALU LINTAS (Studi Kasus di Wilayah Hukum Kepolisian Resor Batu) - Dany Hanggoro (Fakultas Hukum Universitas Islam Malang, 2022)
ABSTRACTThis research is motivated by the number of traffic violations that occur in the jurisdiction of the Batu Police, but enforcement cannot reduce the number of traffic violations. The issues raised were regarding: the role of the Kamsel Unit through the Traffic Dikmas as an effort to reduce the number of traffic violations in the Batu Police jurisdiction, supporting and inhibiting factors, and efforts. Empirical juridical research with sociological approach and legislation approach. The result of this study is that the application of the Traffic Dikmas in reducing the number of traffic violations is very important and has a positive impact on the level of traffic violations at the Batu Police. The supporting factor for the implementation of the Social Community Service, namely the LLAJ Forum, is very supportive of the Kamsel Unit, a good response from the school, campus and community. Inhibiting factors: knowledge related to traffic and legal awareness is still lacking, as well as difficulties in determining the target of the Traffic Dikmas. Efforts are being made to overcome these obstacles: synergizing with stakeholders, more intensely providing socialization and counseling, prioritizing the principle of